EP 141. Physiological effects of subthreshold conditioning TMS anterior of the primary motor cortex. Issue 9 (September 2016) - Duesmann, C.; Fricke, C.; Henn, P.; Claßen, J.; Duesmann, C.; Fricke, C.; Henn, P.; Claßen, J.
Abstract : Introduction: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is widely used to treat patients suffering from Parkinson's Disease. Previous studies suggested that DBS effects may be transmitted via cortico-subthalamic projections opening up possibilities to modulate basal ganglia activity using TMS over cortical areas. Also there is evidence suggesting that multifocal DBS of the STN may be more efficient, implying the use of TMS protocols which target more than one cortical motor area. Although TMS over the primary motor cortex (M1) is well characterized, published TMS effects and locations vary for the dorsal premotor cortex (PMd). Our aim was to locate the PMd and investigate effects of dual-site conditioning TMS applied over PMd and M1 for various interstimulus intervals (ISIs). We hypothesized that there may be short latency effects of PMd conditioning (around 6 ms) originating from direct cortico-cortical projections and longer latency effects possibly resulting from subcortical processing. Methods: In a first experiment we located the PMd by probing multiple short latency cortico-cortical interactions between cortical areas anterior of M1 and M1 in a paired-pulse TMS experiment. Motor-evoked potentials were recorded from the APB muscle of the right hand. The coils used allowed for stimulation of the same or very near cortical areas. We applied conditioning stimuli at 80% RMT over 8 sites 0–52 mm anterior of M1. These were followed by test pulses applied at 120% RMT over M1 after ISIs of 2–8 ms and changes in M1 excitability was examined to determine a possible PMd location. In a second experiment we tested whether longer latency effects could be observed by applying conditioning stimuli over the estimated PMd location determined in experiment 1 using ISIs between 14 and 38 ms. Results: 18 healthy participants (age 25.3 ± 4.1 y) took part in the first experiment. We found a significant facilitation for conditioning at 36 mm anterior of M1 with an ISI of 6 ms ( p  = 0.037) Using interpolation we found a cluster of significant data between 30 and 36 mm. 12 subjects participated in the second experiment (age 24.8 ± 3.9 y). Conditioning pulses were applied 32 mm anterior of M1. There was a significant facilitation at an ISIs of 26 ms with 95% RMT ( p  = 0.005). We found known effects conditioning at 0 mm (over M1) for ISIs of 2, 4 ms ( p  < 0.001, SICI), 8 ms ( p  = 0.014, ICF) and 14 to 26 ms (ICF, SICF). Conclusions: We were able to locate a possible effect of PMd conditioning at 30 to 36 mm anterior of M1 consistent with previous studies. Furthermore we were able to show MEP modulation after subthreshold paired-pulse stimulation over this PMd location and M1 for an ISI of 26 ms. Facilitation at this latency may result from modulation of cortico-basal-ganglia-loops consistent with previous findings probing these loops using a combination of TMS and DBS. We plan to use the new stimulation site in a further study to investigate possible therapeutic effects in PD. Supported by Hertie-Stiftung, Cortexplorer (AZ.: P1140048).